Malaysian Islamic capital market : regulatory and legal scaffold altercations in the legal 'Thick" jungle. - Hassan, Rusni; Yusoff, Adnan (IIUM Press, 2011)
Islamic capital market is burgeoning in Malaysian and in the world today. This is evident from the diversified products offered to the patrons. Malaysia has fonnulated a distinctive legal framework for the Islamic capital market which is indeed an exemplary to the rest of the world, which is yet considering doing it, but is deliberating whetherMalaysia has overdone the regulating of Islamic Capital Market or not. The legal infrastructure and the regulatory measures utilized in the Malaysian capital market is indeed worthwhile looking at. This is the only way to appreciate the Malaysian regulatory and the legal infrastructure for the Islamic capital market. The main aim of this paper is to highlight the legal issues confronting the Islamic capital market due to the sparks created whilst operating it parallel with its counterpart, i.e., the conventional capital market. In this paper, the existing Malaysian legal framework for Islamic Capital Market would be discussed in depth to give the readers a vivid picture of it, and whether regulating is scalded or not, would be discussed